Diffusion-weighted magnetic resonance imaging in the detection of residual and recurrent cholesteatoma in children: A systematic review and meta-analysis. (March 2019) - Bazzi, Khalil; Wong, Eugene; Jufas, Nicholas; Patel, Nirmal
Abstract: Objective: To examine the performance of diffusion-weighted magnetic resonance imaging (DW-MRI) in the detection of residual and recurrent cholesteatoma in children. Methods: A systematic review and meta-analysis was conducted as per PRISMA guidelines using the following databases from their date of inception: MEDLINE, PubMed, Embase, Cochrane Library, Web of Science. Bivariate meta-analysis using a random effects model was used to calculate summarized pooled estimates of sensitivity, specificity, and diagnostic odds ratios, using second-look surgery as the gold standard comparison. Results: A total of ten articles (141 cases) were included for qualitative and quantitative analysis. Pooled sensitivity and specificity of non-echo planar imaging (non-EPI) DW-MRI were 89.4% (95%CI 51.9%–98.5%) and 92.9% (95%CI 81.4%–97.5%) respectively. DW-MRI appears limited in its ability to detect lesions less than 3 mm in size. Conclusion: Non-EPI DW-MRI is highly specific but carries uncertain sensitivity in the detection of residual and recurrent cholesteatoma in children. Further research is warranted to determine the specific role of DW-MRI in this patient group, namely when and how often children should be referred for imaging and in which cases the method can be used to completely replace second-look surgery.